Exploring the Role of Pumped Hydro Energy Storage in Nepal’s Renewable Energy Transition: Technical, Economic, and Environmental Perspectives - A Review - Basnet, Aashish; Dulal, Sahitya; Pandey, Sushovan; Lage, Krijal (International Journal on Engineering Technology and Infrastructure Development, 2025)
The global transition to renewable energy is crucial for mitigating climate change and achieving sustainable development goals. Nepal, with its abundant hydropower potential and immense potential for solar and wind energy is well-positioned to lead this shift. However, the variability of solar and wind energy, along with seasonal fluctuations in rivers, necessitates robust energy storage solutions to ensure grid stability. Nepal's vulnerability to natural disasters such as earthquakes, landslides, and floods further exacerbates the challenges, often damaging hydropower infrastructure and disrupting energy production. Pumped Hydro Energy Storage (PHES) emerges as a key solution— technically feasible across more than 2,800 identified sites with combined potential of 50TWh. It can be integrated with existing infrastructure to improve grid flexibility and reliability. Economically, PHES offers a lower lifecycle cost, with reduced environmental mitigation costs, especially in off-river configurations. Environmentally, PHES has a relatively low carbon footprint and, when carefully located, minimizes impacts on biodiversity and water quality. PHES can stabilize the grid, support renewable integration, and reduce import dependency, paving the way for a resilient, low-carbon energy future in Nepal. This review explores the technical feasibility, economic viability, and environmental implications of PHES implementation, while also identifying key areas for future research and policy development to optimize its adoption within Nepal’s unique geographic and socio-economic context. By adopting this technology, Nepal can diversify its energy mix, enhance disaster resilience, and move toward a more sustainable and self-reliant energy future.